Ascorbic acid partly antagonizes resveratrol mediated heme oxygenase-1 but not paraoxonase-1 induction in cultured hepatocytes - role of the redox-regulated transcription factor Nrf2 - Hori Osamu; Hashida Koji; Döring Frank; Schmelzer Constance; Schrader Charlotte; Breckwoldt Dorothea; Boesch-Saadatmandi Christine; Wagner Anika E; Matsugo Seiichi; Rimbach Gerald (BMC, 2011)
Abstract Background Both resveratrol and vitamin C (ascorbic acid) are frequently used in complementary and alternative medicine. However, little is known about the underlying mechanisms for potential health benefits of resveratrol and its interactions with ascorbic acid. Methods The antioxidant enzymes heme oxygenase-1 and paraoxonase-1 were analysed for their mRNA and protein levels in HUH7 liver cells treated with 10 and 25 μmol/l resveratrol in the absence and presence of 100 and 1000 μmol/l ascorbic acid. Additionally the transactivation of the transcription factor Nrf2 and paraoxonase-1 were determined by reporter gene assays. Results Here, we demonstrate that resveratrol induces the antioxidant enzymes heme oxygenase-1 and paraoxonase-1 in cultured hepatocytes. Heme oxygenase-1 induction by resveratrol was accompanied by an increase in Nrf2 transactivation. Resveratrol mediated Nrf2 transactivation as well as heme oxygenase-1 induction were partly antagonized by 1000 μmol/l ascorbic acid. Conclusions Unlike heme oxygenase-1 (which is highly regulated by Nrf2) paraoxonase-1 (which exhibits fewer ARE/Nrf2 binding sites in its promoter) induction by resveratrol was not counteracted by ascorbic acid. Addition of resveratrol to the cell culture medium produced relatively low levels of hydrogen peroxide which may be a positive hormetic redox-signal for Nrf2 dependent gene expression thereby driving heme oxygenase-1 induction. However, high concentrations of ascorbic acid manifold increased hydrogen peroxide production in the cell culture medium which may be a stress signal thereby disrupting the Nrf2 signalling pathway.